2022
DOI: 10.1049/cit2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous air combat decision‐making of UAV based on parallel self‐play reinforcement learning

Abstract: Aiming at addressing the problem of manoeuvring decision-making in UAV air combat, this study establishes a one-to-one air combat model, defines missile attack areas, and uses the non-deterministic policy Soft-Actor-Critic (SAC) algorithm in deep reinforcement learning to construct a decision model to realize the manoeuvring process. At the same time, the complexity of the proposed algorithm is calculated, and the stability of the closed-loop system of air combat decision-making controlled by neural network is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The paper suggested a new methodology that reduces the number of operations required to produce secret keys by utilizing elliptic curve cryptography [54]. The next step has been the presentation of research difficulties and future directions for further developing the suggested system [55,56].…”
Section: Blockchain Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The paper suggested a new methodology that reduces the number of operations required to produce secret keys by utilizing elliptic curve cryptography [54]. The next step has been the presentation of research difficulties and future directions for further developing the suggested system [55,56].…”
Section: Blockchain Technologymentioning
confidence: 99%
“…The article presents a detailed architecture for a blockchain-based UAV communication system and discusses the opportunities and challenges associated with its implementation. [56] 2022 1. This article proposes an autonomous air combat decision-making framework for UAVs based on parallel self-play reinforcement learning.…”
Section: Blockchain Technologymentioning
confidence: 99%
“…Leveraging their synergies in perception, communication, payload capacity and localization, they enhance a system's overall capability, flexibility and adaptability to uncharted terrains, thereby accomplishing tasks that are arduous for a standalone UAV or solitary UGV. Primarily, they have important applications in the fields of intelligent transportation [1], urban cleanliness [2], unknown exploration [3], military [4,5], etc., and related research has been extensively carried out. It is worth noting that UAVs have played a significant role in the COVID-19 pandemic due to isolation security and telemedicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…The soft actor critic (SAC) [32] algorithm, in contrast to deterministic policy algorithms, aims to maximise the cumulative reward regularised by entropy rather than merely the cumulative reward. The SAC algorithm can increase the randomness of action, encouraging the agent to explore throughout the training process, hence speeding up subsequent learning speed [33]. Numerous benchmark studies have demonstrated state-of-the-art performance.…”
Section: Introductionmentioning
confidence: 99%